Rural women's power in South Asia : understanding shakti - Obeng, J. Pashington (New York: Palgrave Macmllan, 2014)
"This book investigates how women's power and caste cleavages often continue to transcend and crosscut the boundaries of caste/tribe, gender, age, class and religion in India, Pakistan and Bangladesh. Building upon recent formulations of South Asian gender discourse, it explores the ways that perceived notions of women and castified geographies are not only structured in complex and localized relationships of dominance, but are also constituted by practices of the state and central governments. By examining both the particularities of local women's efforts to improve themselves and the ways that power is mediated, the author addresses the multiplex ways individuals both adapt and contest the hegemony of the dominant structures"--
includes index
Keywords: Rural women -- Social conditions; Rural women -- Government policy; Women in rural development; Power (Social sciences); Dominance (Psychology); Caste; Social structure; BUSINESS & ECONOMICS / Development / General; POLITICAL SCIENCE / General; SOCIAL SCIENCE / Gender Studies